The Effect of Work Environment and Integrity on Employee Service Motivation at The BPKAD of West Sumatra Province with Organizational Commitment as an Intervening Variable - Latifa, Asma; Erianjoni, Erianjoni (SAFE-Network, 2025)
This study aims to examine the influence of work environment and integrity on service motivation through organizational commitment as an intervening variable at the Regional Financial and Asset Management Agency (BPKAD) of West Sumatra Province. A quantitative approach was employed using survey data collected from 105 employees through a structured questionnaire. Data analysis was conducted using SPSS version 21, including tests for normality, linearity, heteroscedasticity, multicollinearity, and path analysis. The findings indicate that the work environment, integrity, and organizational commitment have a significant positive effect on service motivation. Organizational commitment is found to partially mediate the effect of work environment and integrity on motivation. The adjusted R square value of 0.437 indicates that the three independent variables explain 43.7% of the variance in service motivation. The final path model confirms both direct and indirect relationships among the variables. These findings emphasize the importance of cultivating an ethical and supportive work environment and strengthening employee commitment to enhance service motivation in the public sector. This research contributes to the growing literature on public service motivation and provides practical implications for government agencies aiming to improve employee performance and organizational effectiveness.